A comprehensive - integrated approach on the theory of development law in Indonesia / Amiruddin A. Dajaan Imami and Susi Herawati - Dajaan Imami, Amiruddin A.; Herawati, Susi (2014)
There is a fundamental change of the idea about law and development comes from a prominent Indonesian legal scholar, Mochtar Kusumaatmadja, that law as a tool of social engineering within the Indonesian context. He also stated that law as principles, norms, institutions as well as processes. Moreover he also mentioned that law as a system of norms that could enhance society‟s development. Meanwhile another prominent legal scholars, the late Satjipto Rahardjo, said that law as a system behavior, which he stated that: "Law for human-beings, not the opposite; and Romli Atmasasmita added that law as a system of values which placed "Pancasila‟ as a way of life of Indonesian society. Those three opinions are integrated, comprehensive and complementing each other. The function and role of law in Indonesian development as leitmotif of development processes in achieving development goals in orderly manner, such as prosperity, unity and justice. It could be achieved based on scientific-inter and multidisciplinary- approach, as well as based on integrated sectors. Maximum of 250 words. (Century Gothic, font 9)